MORAL VALUES THROUGH THE VIDEO GAME CAMPAIGN OF RESIDENT EVIL 6 - Muhandra, Aisyah Putri; Sari Dewi, Ratna (Fakultas Sastra UMN AL Washliyah, 2025)
This study aims to achieve two main objectives. First, it identifies the types of moral values embedded in the video game Resident Evil 6 using the theoretical framework by Sulistyorini and Andalas. Second, it examines the relevance of these moral values in contemporary social and political contexts. Employing a qualitative descriptive approach, the research highlights how moral values serve as guidelines for ethical behavior and decision-making, particularly in addressing crises and upholding justice in modern society. Interactive media like Resident Evil 6 integrate these values, reflecting real-world ethical challenges. The findings reveal 17 moral values in the game, including individual values (e.g., responsibility, justice, honesty, obedience, sacrifice, respect, prudence, wisdom) and social values (e.g., empathy, perseverance for the common good, loyalty, helpfulness, fairness, tolerance, trustworthiness), alongside the religious value of faith. These values are expressed through character dialogues and actions. The study concludes that these moral principles remain relevant today, particularly in themes like leadership accountability, collective struggle, justice, cooperation, and ethical decision-making in global crises.